Prevalence of different forms of child maltreatment among Taiwanese adolescents: A population-based study. (April 2015) - Feng, Jui-Ying; Chang, Yi-Ting; Chang, Hsin-Yi; Fetzer, Susan; Wang, Jung-Der
Abstract: Reported cases of child maltreatment are increasing in Taiwan. Yet, comprehensive epidemiological characteristics of adolescents' exposure over the wide spectrum of violence are still lacking. The purpose of this study was to estimate the prevalence and magnitude of child maltreatment among Taiwanese adolescents. A population-based study was conducted with 5, 276 adolescents aged 12–18 from 35 schools in 17 cities and townships to determine the prevalence of five forms of child maltreatment in Taiwan. A total of 5, 236 adolescents completed anonymous, self-report, structured questionnaires. Most adolescents (91%, n  = 4, 788) experienced at least one form of maltreatment with 83% ( n  = 4, 347) exposed during the previous year. Violence exposure was the most common type of child maltreatment experienced, followed by psychological abuse, physical abuse, neglect, and sexual abuse. Adolescents reported an average of 7.4 (SD = 5.87) victimizations over their lifetime and 4.8 (SD = 4.82) victimizations during the past year. Females reported a higher rate of neglect, while males reported a higher rate of sexual abuse. Most of the sexual abuse perpetrators were known by their victims. Adolescents' victimization and polyvictimization from child maltreatment in Taiwan deserves a review and modification of national control and prevention policies.